The impact of communication on healthcare involvement for people living with motor neurone disease and their carers: A longitudinal qualitative study. Issue 6 (21st July 2022) - Paynter, Camille; Mathers, Susan; Gregory, Heidi; Vogel, Adam P.; Cruice, Madeline
Abstract: Background: Communication and cognitive impairments are known barriers to shared decision‐making. Most people diagnosed with motor neurone disease (MND) will develop a motor speech impairment over the disease course. Some will develop cognitive, linguistic or behavioural disturbance. Despite this, the impact of communication and cognitive impairment on personal healthcare decision‐making in MND is not well known. Aims: This exploratory, longitudinal study aimed to capture the perspectives of people living with MND (plwMND) and family members on managing their healthcare with, or in anticipation of, a communication impairment. Methods & Procedures: Semi‐structured interviews and functional assessments were conducted with plwMND and family members over one to three time points between December 2017 and January 2020. Participants were recruited from a specialist MND clinic using a maximum variation sampling approach. Interview transcripts were analysed using trajectory data analysis: a matrix‐based approach for thematic analysis of longitudinal data. The study was underpinned by interpretive descriptive methodology. Outcomes & Results: A total of 19 plwMND with a range of MND phenotypes and 15 family members were recruited. Disease progression and participant withdrawal resulted in attrition, however 12 plwMND and seven family members participated at all three time points. Consistent cognitive screening was not feasible, which limited the opportunity to explore the impact of cognitive change. An overarching theme 'Communicating takes effort' was identified and illustrates the efforts required to compensate for, or circumnavigate, impairments to maintain involvement in healthcare. Assistance from family and accommodation from healthcare professionals (HCPs) was needed for ongoing engagement. Where plwMND were dependent on alternative communication devices, this assistance was essential and primarily carried out by family members. Despite these efforts, the quality, quantity and accuracy of communication were sometimes compromised. Participants equated good communication with receiving good healthcare, and some expressed anxiety in the anticipation of being unable to express their needs to healthcare workers. Conclusion & Implications: Communication impairment has a direct impact on healthcare involvement. This study demonstrates the effort required by plwMND and their carers to maintain or maximize ongoing involvement. This effort may not always be visible to HCPs. This information may prompt clinicians to consider the best ways to conduct clinical consultations to accommodate patients' abilities. Compromised communication experiences can be moderated by accommodations and support from HCPs and appropriate adjustments in the health system. Asking patients about their communication preferences and needs, allowing extra time and conducting multidisciplinary sessions are examples of such support. What this paper adds: What is already known on this subject?: Communication and cognitive impairments are known contributors to negative health outcomes and barriers to shared decision‐making generally. The existing literature in decision‐making in MND does not address the specific impact of these impairments on personal healthcare involvement for plwMND and their carers. What this paper adds to existing knowledge?: This paper reports the findings of a research project that interviewed 19 plwMND and 15 carers on one to three occasions over a 26‐month period to obtain their perspectives of the impact of communication on healthcare involvement. Whilst a priori the intention was to look at both communicative and cognitive decline, only the former was achieved. The effort and often 'invisible' activity undertaken to manage or maintain involvement in healthcare is identified. Communication impairment requires support and accommodation, otherwise healthcare involvement can be compromised. Results show participants may associate effective communication with good healthcare. What are the potential or actual clinical implications of the work?: Clinicians may wish to use these insights from plwMND and their carers to guide adjustments to their professional practice to maximize healthcare involvement for their patients. Tailored education for different healthcare groups is needed to improve understanding of MND‐related communication impairments and supportive strategies so that involvement in healthcare is not compromised.